Canine leishmaniosis and peripheral neuropathy: a lesson from the neurologist - Floriana Gernone; Domenico Otranto; Jairo Alfonso Mendoza-Roldan; Annamaria Uva; Kaspar Matiasek; Andrea Zatelli (Parasites & Vectors)
Abstract Background Canine leishmaniosis (CanL), a sand fly-borne zoonotic disease caused by Leishmania infantum, is potentially lethal in dogs. A similar or slightly higher quantity of antigens over antibodies promotes the formation of soluble circulating immune complexes (sCIC), which are deposited in the capillary wall, causing the inflammatory cascade responsible for clinical manifestations. Nervous system involvement during CanL is rarely reported in both humans and dogs, and the exact underlying process involving the peripheral nervous system (PNS) is still debated in both species. Methods Two male mixed-breed dogs were presented for exercise intolerance, non-ambulatory flaccid tetraparesis and decreased/absent flexor reflexes in all four limbs. Both dogs were seropositive for L. infantum and presented clinicopathological abnormalities suggestive of active CanL. One dog had received N-methyl-glucamine antimoniate two months before presentation without neurological improvement. Results Generalized PNS involvement was confirmed in both dogs. Biopsies of muscle and nerve tissues showed mononuclear cell inflammatory infiltration, and quantitative real-time polymerase chain reaction (PCR) was positive for Leishmania spp. In addition, Leishmania spp. antigen was detected in the nerve from one dog by immunohistochemistry. Both dogs were started on N-methyl-glucamine antimoniate and allopurinol in association with immunosuppressive corticosteroid therapy, recovering in few weeks. Conclusions Peripheral neuropathies during active CanL can be a consequence of sCIC deposition on endoneurial vascular endothelium comprising the blood–nerve barrier and its consequent breakdown. However, an abnormal host immune response triggered by L. infantum causing demyelination and/or axonal disruption is also possible. The positive response to the immunosuppressive therapy further supports an immune-mediated origin of the PNS condition. Therefore, CanL should be included in the differential diagnosis of PNS disease in dogs, especially in areas endemic for L. infantum. Graphical Abstract